Seasonal dynamics of plankton in relation to some environmental factors in a Beel ecosystem - Chowdhury, MMR; Mondol, MRK; Dewan, S (University Journal of Zoology, Rajshahi University, 2009)
Seasonal dynamics of plankton, water temperature, conductivity, pH, total alkalinity, phosphatephosphorus and nitrate-nitrogen of Burulia beel were measured. These values were within the acceptable ranges. In the present study, water temperature, pH, Nitrate-nitrogen, Phosphate-phosphorus were found to range from 13.50 to 30.50Â°C, 6.21 to 7.33, 1.36 to 2.85 mg/l and 0.07 to 0.71 mg/l, respectively. The range of total plankton was from 12.67Ã105 to 80.83Ã105 cells/l with mean value 29.71Â±19.98Ã105 cells/l. A total of 47 genera of plankton was recorded belonging to Chlorophyceae, Bacillariophyceae, Cyanophyceae, Euglenophyceae, Dinophyceae, Crustacea and Rotifera. Among phytoplanktonic Chlorophyceae was the most dominant group contributing 46% of the total. Cyanophyceae was the least dominant group. From zooplankton, Crustacea was the most dominant group contributing 71% of the total zooplankton. The greatest abundance of phytoplankton was recorded in September to November with an average number 70.67Ã105 cells/l and the minimum in April with an average number 38.33Ã105 cells/l. The abundance of zooplankton showed two peaks, one in the months of August-October and another in the months of April-June. Phytoplankton and zooplankton have a direct relationship with each other. Key words: Burulia beel, phytoplankton, zooplankton Â Â Â doi:10.3329/ujzru.v27i0.1955 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 55-58